John Stuart Mill and Representative Government - Thompson, Dennis F. (Dennis Frank), 1940- (Book collections on Project MUSE., 1976)
Although Mill regarded Considerations on Representative Government as a mature statement of his theory of democracy, critics have tended to treat it less seriously than most of his other major works. Dennis Thompson argues that this neglect has led to inadequate interpretations of Mill's thought on democracy. Drawing where appropriate on other writings by Mill, the author restores a balanced view by studying the structure of the theory expounded in Representative Government. Representative Government is shown to be more coherent and systematic than has generally been assumed. In the first t.